Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1534/g3.118.200778
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Methodology for the Generation of Knockout Deletions in Caenorhabditis elegans

Abstract: The Caenorhabditis elegans Gene Knockout Consortium is tasked with obtaining null mutations in each of the more than 20,000 open reading frames (ORFs) of this organism. To date, approximately 15,000 ORFs have associated putative null alleles. As there has been substantial success in using CRISPR/Cas9 in C. elegans, this appears to be the most promising technique to complete the task. To enhance the efficiency of using CRISPR/Cas9 to generate gene deletions in C. elegans we provide a web-based interface to acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 45 publications
3
89
1
Order By: Relevance
“…Various protocols now incorporate variations, including injection of the Cas9 protein and/or purified sgRNA (Kim & Colaiácovo, ). Innovations and adaptations of CRISPR/Cas9 technologies comprise the inclusion of LoxP/Cre sites on recombination templates (to allow removal of selection markers from established knock‐in/out lines) and the SapTrap system derived from GoldenGate cloning, which provides a simple way to make a variety of knock‐in/out repair constructs (Au et al., ; Schwartz & Jorgensen, ). CRISPR interference and CRISPR activation (CRISPRi and CRISPRa, respectively) have also been successful in C. elegans (Long et al., ; Savell et al., ).…”
Section: New Ways Worms Are Being Usedmentioning
confidence: 99%
“…Various protocols now incorporate variations, including injection of the Cas9 protein and/or purified sgRNA (Kim & Colaiácovo, ). Innovations and adaptations of CRISPR/Cas9 technologies comprise the inclusion of LoxP/Cre sites on recombination templates (to allow removal of selection markers from established knock‐in/out lines) and the SapTrap system derived from GoldenGate cloning, which provides a simple way to make a variety of knock‐in/out repair constructs (Au et al., ; Schwartz & Jorgensen, ). CRISPR interference and CRISPR activation (CRISPRi and CRISPRa, respectively) have also been successful in C. elegans (Long et al., ; Savell et al., ).…”
Section: New Ways Worms Are Being Usedmentioning
confidence: 99%
“…We used CRISPR-Cas9 genome engineering to generate in locus deletions to remove the C-terminal exons specific for the Sgg-PA or Sgg-PB proteoform families. We completely removed the unique exons, replacing them with a 3Px3 driven DsRED marker, flanked by LoxP sites, that was subsequently removed by the activity of Cre recombinase to leave the remainder of the locus largely unaltered [44].…”
Section: Isoform Specific Null Allelesmentioning
confidence: 99%
“…168 The Moerman lab guide selection tool (http://genome.sfu.ca/crispr/) was used to identify the nlg-1 targeting sgRNA. 53 The nlg-1 sgRNA sequence: TCACCAACGTGTCCACGTCA was cloned into the pU6::klp-12 sgRNA vector (obtained from Calarco lab) using site-directed mutagenesis and used for all editing experiments. The nlg-1::AID::GFP::nlg-1 upstream and nlg-1 3' UTR downstream homology arms were synthesized by IDT and cloned into the loxP_myo2_neoR repair construct (obtained from Calarco lab) using Gibson Assembly.…”
Section: Strain and Plasmid Generationmentioning
confidence: 99%
“…Further, CRISPR-Cas9 genome engineering has proven to be reliable and efficient in C. elegans, and unlike most organisms analyzed to date, multiple rigorous whole-genome sequencing studies have revealed no evidence of significant off-target effects due to CRISPR-Cas9 genome editing in this organism. 44,[53][54][55][56][57][58][59] Finally, we developed the Multi-Worm Tracker (MWT), a machine vision system that allows for comprehensive phenotypic analysis of large populations of freely behaving animals while they perform complex sensory and learning behaviors. 60,61 Multiplexing by running several trackers in parallel allows for analysis of multiple measures of morphology, locomotion, mechanosensory sensitivity, as well as several forms of learning in hundreds of animals simultaneously.…”
Section: Introductionmentioning
confidence: 99%